2010
DOI: 10.2337/dc09-1799
|View full text |Cite
|
Sign up to set email alerts
|

Increased Toll-Like Receptor (TLR) Activation and TLR Ligands in Recently Diagnosed Type 2 Diabetic Subjects

Abstract: OBJECTIVEIndividuals with type 2 diabetes have a myriad of metabolic aberrations including increased inflammation, increasing their cardiovascular risk. Toll-like receptors (TLRs) and their ligands play a key role in insulin resistance and atherosclerosis. However, there is a paucity of data examining the expression and activity of TLRs in type 2 diabetes. Thus, in the present study, we examined TLR2 and TLR4 mRNA and protein expression, their ligands, and signaling in monocytes of recently diagnosed type 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
394
3
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(450 citation statements)
references
References 26 publications
33
394
3
15
Order By: Relevance
“…Second, HSP70 activation of the TLR4 ligand on CD4 1 CD25 1 T cells is attributed to an increase in suppressive activity of these T cells in atherosclerosis. 82,83 Furthermore, HSP70 has been indicated to have a negative feedback effect on NF-kB signaling activity. 84 HSP70 has also been demonstrated to switch off TNF receptor-associated factor 6.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%
“…Second, HSP70 activation of the TLR4 ligand on CD4 1 CD25 1 T cells is attributed to an increase in suppressive activity of these T cells in atherosclerosis. 82,83 Furthermore, HSP70 has been indicated to have a negative feedback effect on NF-kB signaling activity. 84 HSP70 has also been demonstrated to switch off TNF receptor-associated factor 6.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%
“…Some evidence indicates that the TLR4 levels are elevated in diabetes and its complications [11][12][13] . The increased expression of TLR4 induced by hyperglycemia results in the generation and secretion of a series of proinflammatory cytokines in adipocytes, monocytes, macrophages, and glomerular endothelial cells, among others [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Th us TLR2 and TLR4 have been implicated to participate in progress of insulin resistance (Shi et al 2006). Hyperglycemia is associated with their stimulation and studies have demonstrated they are overexpressed in patients with diabetes -both the type 1 ) and the type 2 (Dasu et al 2010).…”
mentioning
confidence: 99%